Taxonomic study of the genus Eloeophila Rondani, 1856 of Japan (Limoniidae, Diptera) - Kato, Daichi (Zootaxa, 2021)
Japanese species of the genus Eloeophila are revised. Five new species, E. apicisetula sp. nov., E. canidorsalis sp. nov., E. enischnophallus sp. nov., E. hadrophallus sp. nov., and E. tergilobellus sp. nov. are described. One subspecies and two species are synonymized, E. subaprilina yezoensis (Alexander, 1924) with the nominotypical subspecies, E. hidana (Alexander, 1970) with E. persalsa (Alexander, 1940), and E. mishimai (Alexander, 1969) with E. kintaro (Alexander, 1957). Images of the habitus and wings, and drawings of the male terminalia of the Japanese species are shown. Distributions and a key to the Japanese species are provided.